There is no interest in precious stones in a vegetable market: the life and sermons of Rabbi Jacob Gordon of Toronto - Caplan, Kimmy (Canadian Jewish Studies / Études juives canadiennes, 2006)
A preliminary examination of Rabbi Jacob Gordon’s sermons within their biographical, communal, religious, historical, social, and cultural contexts, offers insight into the challenges Jewish immigrants faced in early twentieth century Toronto—as this Orthodox immigrant rabbi perceived them. These sermons provide details and perspectives, and they particularly illuminate doings within Toronto’s Orthodox-immigrant Jewish community. Gordon’s East-European background did not hold him back from remolding his style, as well as the content of his sermons, fully aware as he was of the need to modify his sermonic approach to respond to the novelties of Toronto’s immigrant world. Gordon’s sermons may also be compared to those of other North American contemporaries, again signaling the unique aspects of the Canadian Jewish religious experience at a critical moment.